Serum Oxidative Stress Biomarkers as Prognostic Indicators of Tumor Aggressiveness in Ovarian Cancer: A Multicenter Clinical Study - Humera Khan, Nishat Afroz, Maria Mehmood, Aisha Taj, Hafsa Sharif, Firdous Ara, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ovarian cancer remains the most lethal gynecologic malignancy, largely due to delayed diagnosis and the aggressive nature of advanced tumors. Emerging evidence suggests that oxidative stress plays a critical role in tumorigenesis and progression. However, the relationship between oxidative stress biomarkers and tumor aggressiveness in ovarian cancer remains underexplored, particularly in South Asian populations. Objective: To evaluate the association between serum oxidative stress biomarkers and tumor aggressiveness in ovarian cancer patients. Methods: This cross-sectional study was conducted from July 2022 to February 2023 at Shahbaz Sharif Hospital Multan, Liaquat National Hospital Karachi, and BMC Sandeman Provincial Hospital Quetta. Eighty histologically confirmed ovarian cancer patients aged 25–70 years were enrolled prior to therapy. Serum levels of malondialdehyde (MDA), total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were measured. Tumor grade and FIGO stage were used to define aggressiveness. Statistical analyses included t-tests and Pearson’s correlation. Results: High-grade and advanced-stage tumors showed significantly elevated MDA levels (p<0.001) and decreased TAC, SOD, and GPx (all p<0.001). MDA positively correlated with tumor grade (r=0.69) and stage (r=0.72), while antioxidant markers showed negative correlations (p<0.001). Conclusion: Oxidative stress is strongly associated with increased tumor aggressiveness in ovarian cancer. Serum oxidative biomarkers may serve as valuable prognostic indicators and therapeutic targets. Further longitudinal studies are warranted to validate these findings and explore antioxidant-based interventions in clinical practice. Keywords: Ovarian Cancer, Oxidative Stress, Malondialdehyde, Superoxide Dismutase, Glutathione Peroxidase, Tumor Grade, FIGO Stage.